Investigation of the geometry changes of body legs with compression stocking in static position - Olena Kyzymchuk; Yordan Kyosev; Liudmyla Melnyk; Natalija Sadretdinova (Communications in Development and Assembling of Textile Products, 2023)
The high speed (4D) body scanning provides technical possibility for accurate measurements of the body geometry and can be applied not only for moving objects, but as well for evaluating the changes of static geometry with time. This information is important for compression socks, because it provides data regarding the relaxation processes of the textile product and of the human leg. In this work, changes of the body geometry after 1 and 4 hours with compression socks are investigated. Up to 9% changes of the cross section areas and up to 5.5% of changes of the circumference between the position at the starting point and after 4 hours are detected. Additionally the differences between the both legs of the investigated person and of the different (upper- and bottom) part of the leg are observed. It is the first step to the digitalization of the personal compression stocking design.